Catalytic Transfer of Magnetism using a Neutral Iridium Phenoxide Complex - Ruddlesden, Amy J (Organometallics, 2015)
A novel neutral iridium carbene complex Ir(κC,O-L1)(COD) (1) [where COD = cyclooctadiene and L1 = 3-(2-methylene-4-nitrophenolate)-1-(2,4,6-trimethylphenyl) imidazolylidene] with a pendant alkoxide ligand has been prepared and characterized. It contains a strong Ir-O bond and X-ray analysis reveals a distorted square planar structure. NMR spectroscopy reveals dynamic solution state behavior commensurate with rapid seven-membered ring flipping. In CD2Cl2 solution, under hydrogen at low temperature, this complex dominates although it exists in equilibrium with a reactive iridium dihydride cyclooctadiene complex. 1 reacts with pyridine and H2 to form neutral Ir(H)2(κC,O-L1)(py)2 which also exists in two conformers that differ according to the orientation of the seven-membered metallocycle and whilst its Ir-O bond remains intact, the complex undergoes both pyridine and H2 exchange. As a consequence, when placed under parahydrogen, efficient polarization transfer catalysis (PTC) is observed via the Signal Amplification By Reversible Exchange (SABRE) approach. Due to the neutral character of this catalyst, good hyperpolarization activity is shown in a wide range of solvents for a number of substrates. These observations reflect a dramatic improvement in solvent tolerance of SABRE over that reported for the best PTC precursor IrCl(IMes)(COD). For THF, the associated 1H NMR signal enhancement for the ortho proton signal of pyridine shows an increase of 600-fold at 298 K. The level of signal enhancement can be increased further through warming or varying the magnetic field experienced by the sample at the point of catalytic magnetization transfer